AB1235 SALIVARY LEVEL OF CALPROTECTIN (MRP 8/14) AS A BIOMARKER FOR SJÖGREN SYNDROME – A PROSPECTIVE OBSERVATIONAL STUDY. (13th June 2020) - Chebbi, P.; Kabeer, J.; Sandhya, P.; Gowri, M.; Danda, D.
Abstract : Background: Objectives: Calprotectin (MRP 8/14) is secreted by neutrophils and monocytes in an inflammatory milieu(1). Increased levels of calprotectin in blood and faeces has been previously shown in patients with primary Sjogren's syndrome(pSS)(2). We hypothesised Calprotectin in saliva may therefore potentially reflect inflammation in salivary glands. In the present study, we aimed to assess the utility of salivary calprotectin as a biomarker in pSS and to evaluate the potential association of calprotectin with clinical features, laboratory markers and disease activity indexes in pSS. Methods: Consecutive patients attending rheumatology clinic between September 2016 and July 2017 of age more than 18 years fulfilling either American European Consensus Group (AECG) 2002 or 2016 American College of Rheumatology/European League Against Rheumatism Classification Criteria for Primary Sjogren's Syndrome, constituted the case group. Patients with sicca non-pSS and rheumatoid arthritis patients satisfying ACR/EULAR criteria 2010 were recruited as disease controls. Age and sex-matched healthy subjects were recruited as a controls. Patient history, signs and symptoms, laboratory investigations, ESSDAI and ESSPRI scoring were noted for cases and disease controls. Unstimulated saliva was collected by the spitting method. Salivary calprotectin levels were quantified by commercially available ELISA kit(R&D Systems, MN, USA). Results: A total of 42 pSS cases (41.59 11.21 years, 40 women), 40 disease controls (47.62 9.81 years, 39 women) and 30 healthy controls (36 10.65 years, 29 women) were recruited. In pSS and disease controls, the median levels of salivary calprotectin [38.5(81) and 52(69.5 ng/ml)] were significantly higher compared to healthy controls [26.5(29) p=0.001]. Salivary calprotectin levels in pSS was positively associated with oral symptoms and negatively associated with immunosuppression of 1 year and more(P=0.04 and 0.03 respectively), but not ESSDAI, ESSPRI scores or lab parameters. Conclusion: Salivary calprotectin was elevated in pSS compared to healthy subjects and was found to be positively associated with oral symptoms and with immunosuppressive treatment. References: [ 1]Stroncek DF, Shankar RA, Skubitz KM. The subcellular distribution of myeloid-related protein 8 (MRP8) and MRP14 in human neutrophils. J Transl Med. 2005 Sep 28;3:36. [2]Fagerhol MK, Larsen A, Brun JG, Hammer HB, Angel K, Kvien TK, et al. Large molecular size EDTA-resistant complexes containing S100A12, ERAC, in serum during inflammatory conditions. Scand J Clin Lab Invest. 2012 Apr;72(2):129–36. Disclosure of Interests: None declared